Optimalisasi Penerapan Dietary Approaches to Stop Hypertension (Dash) Berbasis Kearifan Lokal pada Penderita Hipertensi - Asri Aprilia Rohman; Tita Rohita; Yoga Ginanjar; Asep Wahyudin; Ana Samiatul Milah; Muhamad Rovi; Rifa Lasriani; Muhamad Hafiz; Gita Agustina; Dea Dea (Yayasan Inspirasi El Burhani, 2023)
Introduction: Data from the World Health Organization (WHO) 2015 states that hypertension kills 9.4 million every year. Hypertension sufferers reach 1.13 billion people in the world. It is estimated that this number will increase significantly. In 2025 it is estimated that 29% or around 1.15 billion people will suffer from hypertension (Ministry of Health RI, 2018). In Indonesia, there are 70 million people with hypertension and 24% have controlled hypertension. The prevalence in adults is 6-15% (Department of the Republic of Indonesia Ministry of Health, 2019). Objective: Participants in this activity totaled 95 people with an age range of 40 to 75 years. Method: This community service goes through several methods and stages consisting of the preparation stage and the activity stage. Result: Based on the results of the training, it was found that there was an increase in knowledge with an average increase in post-test results of 17.2 with the highest score in the post-test being 100. Conclusion: Based on community service, an overview of the understanding of the implementation of DASH in hypertensive patients was obtained, namely that after being given education, the number increased significantly. Continuous education is carried out to remind that hypertension is a chronic disease that results in complications and requires adherence to diet and drug management as well as changes in lifestyle that are carried out throughout his age.